2018
DOI: 10.1037/apl0000324
|View full text |Cite
|
Sign up to set email alerts
|

Is perfect good? A meta-analysis of perfectionism in the workplace.

Abstract: Although the concept of perfectionism is familiar to most people, its relationships with organizationally relevant variables remain unclear because of the dispersed and multidisciplinary nature of extant research. The state of the literature is particularly concerning given the likely widespread influence perfectionism has on individuals' workplace attitudes and behaviors. Moreover, research in multiple disciplines of psychology has revealed the phenomenon of perfectionism to be multidimensional. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 153 publications
5
103
4
2
Order By: Relevance
“…This result extended prior evidence on effects of DPC on average levels of work‐related worry and rumination (Flaxman et al, , ) and on associations between perfectionistic cognitions and negative forms of perseverative thinking (not differentiating between PSC and PCC; Flett, Hewitt, Blankstein, & Gray, ; Flett, Madorsky, Hewitt, & Heisel, ) to specifically investigating fluctuations in perfectionistic concerns in the form of current thoughts on the within‐person level. In contrast to our expectations and to evidence on the role of trait perfectionism in the workplace (see Harari et al, and Ocampo et al, for recent reviews), that consistently reported detrimental effects of perfectionistic concerns not only on indicators of strain and organizational behavior but also on motivational variables and detachment, we found no evidence that associations between the two dimensions of dispositional perfectionism and psychological detachment were different from zero at the between‐persons level. This was surprising given Flaxman and colleagues' (Flaxman et al, , ) results because they found that DPC and DPS were associated with unique forms of cognitive work‐related behavior during evening leisure time (i.e., DPC with work‐related worry/rumination but not positive thinking about work and DPS with positive thinking about work but not work‐related worry/rumination).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result extended prior evidence on effects of DPC on average levels of work‐related worry and rumination (Flaxman et al, , ) and on associations between perfectionistic cognitions and negative forms of perseverative thinking (not differentiating between PSC and PCC; Flett, Hewitt, Blankstein, & Gray, ; Flett, Madorsky, Hewitt, & Heisel, ) to specifically investigating fluctuations in perfectionistic concerns in the form of current thoughts on the within‐person level. In contrast to our expectations and to evidence on the role of trait perfectionism in the workplace (see Harari et al, and Ocampo et al, for recent reviews), that consistently reported detrimental effects of perfectionistic concerns not only on indicators of strain and organizational behavior but also on motivational variables and detachment, we found no evidence that associations between the two dimensions of dispositional perfectionism and psychological detachment were different from zero at the between‐persons level. This was surprising given Flaxman and colleagues' (Flaxman et al, , ) results because they found that DPC and DPS were associated with unique forms of cognitive work‐related behavior during evening leisure time (i.e., DPC with work‐related worry/rumination but not positive thinking about work and DPS with positive thinking about work but not work‐related worry/rumination).…”
Section: Discussioncontrasting
confidence: 99%
“…Although we caution against overinterpreting this single and small effect, it might be explained against the background of research that has frequently revealed more positive associations of perfectionistic strivings with psychological adjustment, especially when the overlap with perfectionistic concerns was controlled for (e.g., Prestele & Altstötter‐Gleich, ; Stoeber & Gaudreau, ; Stoeber, ). More specifically, such less detrimental effects of perfectionistic strivings compared to perfectionistic concerns were also reported for indicators of distress and detachment in the workplace (see Harari, Swider, Steed, & Breidenthal, and Ocampo, Wang, Kiazad, Restubog, & Ashkanasy, for recent reviews). Although we aimed to assess a lack of psychological detachment in a broader sense, that is, meaning both positive and negative engagement in work‐related activities during evening leisure time, participants may have predominantly based their judgments on negative activities.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This result extended prior evidence on effects of DPC on average levels of work-related worry and rumination (Flaxman et al, 2017(Flaxman et al, , 2012 and on associations between perfectionistic cognitions and negative forms of perseverative thinking (not differentiating between PSC and PCC; Flett et al, 1998;Flett et al, 2002) to specifically investigating fluctuations in perfectionistic concerns in the form of current thoughts on the within-person level. In contrast to our expectations and to evidence on the role of trait perfectionism in the workplace (see Harari et al, 2018 andOcampo et al, 2019 for recent reviews), that consistently reported detrimental effects of perfectionistic concerns not only on indicators of strain and organizational behavior but also on motivational variables and detachment, we found no evidence that associations between the two dimensions of dispositional perfectionism and psychological detachment were different from zero at the between-persons level. This was surprising given Flaxman and colleagues' (Flaxman et al, 2017(Flaxman et al, , 2012 results because they found that DPC and DPS were associated with unique forms of cognitive work-related behavior during evening leisure time (i.e., DPC with work-related worry/rumination but not positive thinking about work and DPS with positive thinking about work but not work-related worry/rumination).…”
Section: The Role Of Perfectionism In the Sd Modelcontrasting
confidence: 99%
“…Although we caution against overinterpreting this single and small effect, it might be explained against the background of research that has frequently revealed more positive associations of perfectionistic strivings with psychological adjustment, especially when the overlap with perfectionistic concerns was controlled for (e.g., Stoeber & Gaudreau, 2017Stoeber et al, 2014). More specifically, such less detrimental effects of perfectionistic strivings compared to perfectionistic concerns were also reported for indicators of distress and detachment in the workplace (see Harari, Swider, Steed, &Breidenthal, 2018 andOcampo, Wang, Kiazad, Restubog, &Ashkanasy, 2019 for recent reviews). Although we aimed to assess a lack of psychological detachment in a broader sense, that is, meaning both positive and negative engagement in work-related activities during evening leisure time, participants may have predominantly based their judgments on negative activities.…”
Section: The Role Of Perfectionism In the Sd Modelmentioning
confidence: 88%